Adverse cardiovascular outcomes and their relationship with risk factors according to the prospective study MERIDIAN-RO - E. V. Filippov; A. N. Vorobyev; N. V. Dobrynina; L. A. Zotova; E. V. Lygina; N. N. Nikulina; S. V. Seleznev; S. S. Yakushin (Российский кардиологический журнал)
Aim. To assess the incidence of adverse outcomes and the role of main risk factors in their development.Material and methods. Prospective, long-term study was conducted with observation period of 36 months. The sample in the MERIDIAN-RO study was formed from the urban and rural population. It included 1622 people aged 25-64 years. The response to the study was 86,1%. Observation and screening of endpoints continued for 36 months. The endpoints were: all-cause death, ischemic stroke, myocardial infarction, coronary artery revascularization.Results. When studying the relationship between various risk factors and outcomes, it was found that they had a significant impact on the combined endpoint (all-cause death + nonfatal ischemic stroke + nonfatal myocardial infarction): risk SCORE >5% (odds ratio (OR) 5,80, 95% confidence interval (CI) 2,31-14,58, p=0,0001, Wald — 23,040), excessive alcohol consumption (OR 714, 95% CI 1,41-36,31, p=0,018, Wald — 2,908), arterial hypertension (OR 4,77 95% CI 1,91-11,90, p=0,01, Wald — 9,000), combination of coronary artery disease/myocardial infarction/stroke in history (OR 11,16, 95% CI 3,98-31,31, p=0,0001, Wald — 22,607) and an apolipoprotein B increase more than 180 mg/dL (OR 28,57 95% CI 732-111,42, p=0,0001, Wald — 24,509).Conclusion. The most significant effect on the combined endpoint (all-cause death + nonfatal myocardial infarction + nonfatal stroke) made: SCORE risk >5%, excessive alcohol consumption, hypertension, combination of coronary artery disease/myocardial infarction/stroke in history and an apolipoprotein B increase more than 180 mg/dL. That should be considered when choosing aims and preventive strategies.